Successful Treatment of Granulomatous Rosacea by JAK Inhibitor Abrocitinib: A Case Report - Ren M; Yang X; Teng Y; Lu W; Ding Y; Tao X (Clinical, Cosmetic and Investigational Dermatology, 2023)
Mingyang Ren,1 Xianhong Yang,2 Yan Teng,2 Wei Lu,2 Yang Ding,2 Xiaohua Tao2 1Department of Graduate School, Bengbu Medical College, Bengbu, People’s Republic of China; 2Center for Plastic & Reconstructive Surgery, Department of Dermatology, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital, Hangzhou Medical College), Hangzhou, People’s Republic of ChinaCorrespondence: Xiaohua Tao, Email txhtxh@sina.comAbstract: Granulomatous rosacea (GR) is a rare inflammatory skin disease characterized by persistent, hard, yellow, brown, red, or flesh-colored papules, plaques, or nodules on the face. Limited data are available on patients treated for GR, with only case reports and case series published. Herein, we describe the case of a 53-year-old woman who presented to the hospital with persistent red to brown and pink patches on both cheeks accompanied by a burning sensation for one month. Histopathological examination of a cutaneous biopsy revealed granulomatous inflammation in focal areas. Both acid-fast and Periodic acid-Schiff staining were negative. The patient was diagnosed with GR based on her clinical presentation and laboratory test results. She was treated with abrocitinib, a JAK-1 inhibitor, for 20 weeks. This resulted in substantial improvement in her rash and the associated burning sensation. Subsequent follow-up visits indicated no adverse effects or relapses. Additionally, a literature review was conducted to compare with the current case, which concluded that abrocitinib is a viable treatment option for GR, exhibiting a relatively high safety profile with minimal side effects.Keywords: JAK inhibitor, granulomatous rosacea, abrocitinib, efficacy